Assessing the professional performance of UK doctors: an evaluation of the utility of the General Medical Council patient and colleague questionnaires. Issue 3 (2nd June 2008) - Campbell, J L; Richards, S H; Dickens, A; Greco, M; Narayanan, A; Brearley, S
Abstract : Objective: To investigate the utility of the GMC patient and colleague questionnaires in assessing the professional performance of a large sample of UK doctors. Design: Cross-sectional questionnaire surveys. Setting: Range of UK clinical practice settings. Participants: 541 doctors gave preliminary agreement to take part in the study. Responses were received from 13 754 patients attending one of 380 participant doctors, and from 4269 colleagues of 309 participant doctors. Main outcome measures: Questionnaire performance and standardised scores for each doctor derived from patient and colleague responses. Results: Participant doctors were similar to non-participants in respect of age and gender. The patient and colleague questionnaires were acceptable to participants as evidenced by low levels of missing data. One patient questionnaire item seemed to cause confusion for respondents and requires rewording. Both patient and colleague responses were highly skewed towards favourable impressions of doctor performance, with high internal consistency. To achieve acceptable levels of reliability, a minimum of 8 colleague questionnaires and 22 patient questionnaires are required. G coefficients for both questionnaires were comparable with internationally recognised survey instruments of broadly similar intent. Patient and colleague assessments provided complementary perspectives of doctors' performance. Older doctors had lower patient-derived and colleague-derived scores than younger doctors. Doctors from a mental health trust and doctors providing care in a variety of non-NHS settings had lower patient scores compared with doctors providing care in acute or primary care trust settings. Conclusions: The GMC patient and colleague questionnaires offer a reliable basis for the assessment of professionalism among UK doctors. If used in the revalidation of doctors' registration, they would be capable of discriminating a range of professional performance among doctors, and potentially identifying a minority whose practice should to subjected to further scrutiny.